Surgical treatment of liver tumors – own experience and literature review - Tarasik, Aliaksandr; Jaroszewicz, Jerzy; Januszkiewicz, Marcin (Clinical and Experimental Hepatology, 2017)
Despite advances, the treatment of focal liver lesions is still challenging. It requires the experience of a surgeon, improvement of existing and the development of new techniques. The aim of this article is to present a literature review and summarize our experience in liver surgery. Twenty-one patients with various liver tumors were treated in 2015 at the Department of Surgical Oncology of Bialystok Center for Oncology. Mostly patients were diagnosed with colorectal cancer liver metastases or hepatocellular carcinoma. Nine anatomical, 6 non-anatomical resections and 6 radiofrequency ablations were performed. Among 9 resections, 6 bisegmentectomies, resection of the 4b segment, and left-side and right-side hemihepatectomy were performed. Resections were associated only with minor postoperative complications. No perioperative mortality was noted. Preliminary outcomes of resections and radiofrequency ablations of liver lesions even in a low volume surgical center are promising and are associated with a relatively low rate of complications.